2017
DOI: 10.1002/rse2.49
|View full text |Cite
|
Sign up to set email alerts
|

Influence of artefacts in marine digital terrain models on habitat maps and species distribution models: a multiscale assessment

Abstract: Remote sensing techniques are currently the main methods providing elevation data used to produce Digital Terrain Models (DTM). Terrain attributes (e.g. slope, orientation, rugosity) derived from DTMs are commonly used as surrogates of species or habitat distribution in ecological studies. While DTMs' errors are known to propagate to terrain attributes, their impact on ecological analyses is however rarely documented. This study assessed the impact of data acquisition artefacts on habitat maps and species dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 78 publications
(153 reference statements)
0
30
0
2
Order By: Relevance
“…However, errors and uncertainty can result in inaccurate representation of the environments, and thus inaccurate maps (Wintle et al, 2005, Figure 3). While looking at the impact of artifacts in bathymetric data on the habitat mapping workflow, Lecours et al (2017a) found that poor data quality affects the outcome of the mapping process, although in an often unpredictable way: the presence of artifacts can sometimes artificially increase the measured map accuracy and model predictive power while in other cases it can decrease them. A lack of awareness and understanding of the concepts associated with data quality can in turn lead to misinformed conservation and management decisions (Rondinini et al, 2006;Beale and Lennon, 2012;Katsanevakis et al, 2012) with dire results for biodiversity (Regan et al, 2005).…”
Section: Data Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…However, errors and uncertainty can result in inaccurate representation of the environments, and thus inaccurate maps (Wintle et al, 2005, Figure 3). While looking at the impact of artifacts in bathymetric data on the habitat mapping workflow, Lecours et al (2017a) found that poor data quality affects the outcome of the mapping process, although in an often unpredictable way: the presence of artifacts can sometimes artificially increase the measured map accuracy and model predictive power while in other cases it can decrease them. A lack of awareness and understanding of the concepts associated with data quality can in turn lead to misinformed conservation and management decisions (Rondinini et al, 2006;Beale and Lennon, 2012;Katsanevakis et al, 2012) with dire results for biodiversity (Regan et al, 2005).…”
Section: Data Qualitymentioning
confidence: 99%
“…The reference map is the same as in Figure 2. The altered map used bathymetric data impacted by artifacts caused by a 0.25 s mis-synchronization in the surveying system (see Lecours et al, 2017a). The presence of artifacts made the classification vary of 2.1%.…”
Section: Data Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous habitat mapping studies have tested the importance of environmental predictor scale when creating habitat maps [2,3,56]. There have also been a number of studies, primarily terrestrial, that have examined the effects of hierarchical classifications on habitat prediction [33,35,36].…”
Section: Discussionmentioning
confidence: 99%